2021
DOI: 10.1093/jac/dkab123
|View full text |Cite
|
Sign up to set email alerts
|

Presence of HIV-1 G-to-A mutations linked to APOBEC editing is more prevalent in non-B HIV-1 subtypes and is associated with lower HIV-1 reservoir

Abstract: Objectives APOBEC3 editing activity contributes to sequences variation and viral diversification. We aimed to characterize virological and clinical factors associated with G-to-A mutations and stop codons in the HIV-1 reservoir, markers of APOBEC3 footprints, in order to better understand HIV-1 diversity among virologically suppressed HIV-1-infected patients. Methods Immuno-virological and clinical factors were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“… 33 , 34 Some articles also reported that env is prone to mutations, and changes in some bases within env lead to the loss of HIV-1 infection ability. 35 , 36 , 37 The IPDA targets only a segment of env , and mutations in other regions may also cause the inactivation of HIV-1, so we applied monoclonal screening techniques to obtain a larger number of env sequences isolated from HIV-1 patients and constructed pseudoviruses. The env probe binding sites of these pseudoviruses were consistent, but there were many mutations in env gene outside the probe binding site, causing the formation of stop codons that prevent the formation of viruses.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Some articles also reported that env is prone to mutations, and changes in some bases within env lead to the loss of HIV-1 infection ability. 35 , 36 , 37 The IPDA targets only a segment of env , and mutations in other regions may also cause the inactivation of HIV-1, so we applied monoclonal screening techniques to obtain a larger number of env sequences isolated from HIV-1 patients and constructed pseudoviruses. The env probe binding sites of these pseudoviruses were consistent, but there were many mutations in env gene outside the probe binding site, causing the formation of stop codons that prevent the formation of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of a universal assay to quantify the latent reservoir across subtypes could be one of the reasons why only a handful of studies examined the latent reservoir characteristics among the viral subtypes. These assays primarily quantify the reservoir in the proviral DNA Compartment [45,46 ▪ ,47,48]. Despite the low number of such studies on non-B viral reservoirs, interesting observations have been reported, especially when the differences are semi-qualitative.…”
Section: Subtypes and The Latent Viral Reservoirmentioning
confidence: 99%
“…Another interesting observation is the demonstration that the total latent reservoir size in HIV-1B infections is relatively larger than those of non-B infections [45,46 ▪ ,47,48] or comparable [53,54]. Surprisingly, no study demonstrated that the latent reservoir size of HIV-1B is smaller than other subtypes; therefore, caution must be applied while interpreting these results.…”
Section: Subtypes and The Latent Viral Reservoirmentioning
confidence: 99%